Synthesis of Biofoam Based on Starch Mixture of Cassava Peel and Kepok Banana Peel with Chitosan Additive to Improve Mechanical and Physical Characteristics - Darni, Yuli; Anandati, Ghea Maulidaco; Mayanti, Eva; Lismeri, Lia; Utami, Herti; Azhar, Azhar (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2023)
Biodegradable foam(biofoam) is a type of bioplastic that is used as an alternative packaging to replace styrofoam which is safe and environmentally friendly. This study aims to determine the characteristics of biofoam made from cassava peel starch (A) and banana peel starch (B), as well as the effect of adding chitosan to the physical, mechanical, and biodegradation properties of the resulting biofoam. In the manufacture of biofoam, the variation of the A:B ratio used is 1:0; 3:2; 1:1 (%w/w). While the chitosan content added was 0%, 15%, and 30% by weight of starch and blowing agent NaHCO3 with a content of 12% by weight of starch. The production of biofoam was carried out using the thermopressing method with a printing temperature of 125C and a printing time of 7 minutes. The results of biofoam were characterized by density, water absorption, compressive strength, biodegradation, and FTIR functional groups. Based on the research results, it is known that biofoam is close to commercial biofoam standards, namely biofoam with an A:B ratio of 3:2 and the addition of 15% chitosan with a density value of 0.560 g/cm3, the water absorption capacity of 33.68%, compressive strength value of 5, 05 MPa, and the decomposition power of 17.44%. These variations have functional groups NH, OH, CH, C=O, CN, and CO.